PENYUSUNAN ANGGARAN PEMBELIAN BAHAN BAKU KUNYIT PADA PT. NYONYA MENEER SEMARANG - Hafsa Nur Mardiah; Wahyu Hidayat; Handoyo Djoko Waloejo (Universitas Diponegoro, 2013)
PT. Nyonya Meneer Semarang is a company engaged in the production of herbal medicine. Purchases of raw materials performed each year has increased, it is influenced by the increase in market demand and the difference between the purchase of raw materials that have been planned and the actual realization of the need. With a production capacity of more banyyak, budget forecasting is necessary to purchase raw materials with a small degree of inconsistency. So it can reduce the cost of investment in materials, minimize production costs and ultimately company profits can be optimized. The purpose of this study was to determine the determination of the optimal raw material inventory by EOQ. Where the ledge first thing to do is to determine the need for raw materials for 5 (five) years, then the budget budgeting buying raw turmeric which includes the number of needs, beginning inventory and ending inventory so as to know the amount of the purchase of raw materials each year. To determine the need for raw materials in 2012 as a supporting factor is the historical data, data distribution, extensive business and competitors. Therefore used a method of forecasting the trend analysis covering semi average method, least square method, the method and the method of quadratic trend eksponentisial trend. Of the four forecasting methods are then conducted further analysis by selecting the most appropriate method paramalan to search the very low standard deviation, which means having a close measure of the accuracy of the real situation.